Analisis Persepsi Mahasiswa Mengenai Praktik Penggelapan Pajak Berdasarkan Literasi Tarif Pajak dan Sanksi Pajak - Supyan, Ita Suryanita; Oktaviani, Sani (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This research aims to analyze students' perceptions of tax evasion practices based on tax rate literacy and tax sanctions, to identify the barriers students face in perceiving tax evasion based on tax rate literacy and tax sanctions, and to determine ways to address tax evasion practices based on tax rate literacy and tax sanctions. The research design uses a case study approach. Data collection was carried out through interviews, observations, and documentation to gain a deeper understanding of students' views on tax evasion practices. The research findings indicate that good literacy regarding tax rates and tax sanctions has a positive impact on students' perceptions. A thorough understanding of fair tax rates and the consequences of tax violations can reduce the potential for tax evasion and improve compliance with tax obligations. Additionally, this research also found that internal factors, such as students' self-confidence, as well as external factors, such as insights gained from their surroundings and social media, also influence their views on tax evasion practices. The main barriers identified in understanding taxation are the frequently changing tax regulations and the complexity of tax materials. Furthermore, the perception of lectures being less interactive is one of the factors influencing students' understanding. The solution that can be provided is the improvement of more interactive learning and the application of teaching methods that simplify students' understanding of tax regulations and materials. This research is of a qualitative descriptive type.